Exploring the Written Dialogues of Two First-Year Secondary Science Teachers in an Online Mentoring Program - Bang, EunJin; Luft, Julie A. (Journal of science teacher education, 2014)
This study explored the yearlong learning processes of two first-year secondary science teachers participating in an online mentoring program, through examination of their written dialogues within the program and other data. Using a case study method, this study (a) explored the patterns of written dialogues between the two new teachers and their mentors over the course of a year, (b) documented pertinent topics of importance, and finally (c) illustrated the new realities created in the mentees' classrooms as a result of the online mentoring process. Penelope and Bradley, who taught at an urban school and at a suburban school respectively, were selected as subjects. Our analysis revealed that the two pairs of mentee-mentors showed different participation patterns that affected the intensity of the creation of new realities, and affected whether the mentees tried/vetted new teaching practices suggested by their mentors. Yet, analysis also revealed that certain elements in the written dialogues between pairs were found to be similar, in that construction of knowledge was evident between both pairs when friction developed and appropriate teamwork emerged to deal with it. The topics of greatest interest and importance within the dialogues were those related to the logistics of the school system and the processes and methodologies of teaching. These results suggest that online mentoring programs are an effective dialogical tool for transferring the knowledge of experts to novices, and for thus expediting the professional induction and growth of new science teachers.